Fostering entrepreneurship-STEM creative thinking among secondary school students - Sufirman Arifin; Siew Nyet Moi @ Sopiah Abdullah (Scientia Socialis Ltd, 2024)
Fostering creative thinking in facilitating teaching and learning (TL) of entrepreneurship and STEM at the secondary schools is sparsely documented in the literature and warrants further Inquiry. Thus, this research aimed to assess secondary school students’ entrepreneurial STEM creative thinking (E-STEMCT). A comprehensive entrepreneurship-STEM module integrating socio-scientific issues (SSIs) and design thinking (DT) approach was meticulously designed to facilitate TL. A quasi-experimental quantitative study was conducted on 267 Form Four students aged 17 years old enrolled in rural secondary schools. Three intact groups were randomly divided into a) SSIs-DT approach, n=89), b) Design Thinking Approach (DT-A, n=90), and c) Conventional approach (CA, n=88). The E-STEMCT test instrument was developed and applied to measure students’ pre- and post-levels of E-STENCT. Rigorous statistical analysis employing MANCOVA, ANCOVA, and Effect Size techniques was conducted. MANCOVA results revealed statistically significant effects across all TL groups, indicating the effects of the interventions in fostering E-STEMCT. Furthermore, ANCOVA analysis results indicated that the SSIs-DT integration approach significantly increased E-STEMCT and its constructs: Inquiry, New Ideas, Design, Creation, and Commercialization compared to the DT-A and CA approaches. These results support the view that the SSIs-DT integration approach has a positive impact on fostering E-STEMCT among secondary school students.